2007
DOI: 10.1111/j.1540-8167.2007.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Complete Isolation of the Posterior Left Atrium Including Pulmonary Veins for Atrial Fibrillation

Abstract: This study shows that it is possible to achieve complete isolation of the posterior LA including all PVs without posterior vertical lesions. Box isolation is associated with a high clinical success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 29 publications
0
106
0
Order By: Relevance
“…8 In the present study, in addition to the patients with paroxysmal AF, we performed the NCM-guided Box isolation in patients with persistent or longstanding persistent AF, and the success rate of maintaining normal sinus rhythm without any antiarrhythmic drugs was 91%, 73% and 46%, respectively. Monsour et al performed a Fourier analysis of the bi-atrial fibrillatory signals in a sheep model of AF and found that the fastest frequencies recorded during AF occurred in the posterior LA, and that a left-to-right atrial frequency gradient existed during AF.…”
Section: Efficacy Of the Box Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In the present study, in addition to the patients with paroxysmal AF, we performed the NCM-guided Box isolation in patients with persistent or longstanding persistent AF, and the success rate of maintaining normal sinus rhythm without any antiarrhythmic drugs was 91%, 73% and 46%, respectively. Monsour et al performed a Fourier analysis of the bi-atrial fibrillatory signals in a sheep model of AF and found that the fastest frequencies recorded during AF occurred in the posterior LA, and that a left-to-right atrial frequency gradient existed during AF.…”
Section: Efficacy Of the Box Isolationmentioning
confidence: 99%
“…8 Commencing from the lesion at the left inferior PV, the sheath and catheter were rotated clockwise posteriorly and dragged toward the right inferior PV. If AF did not terminate after the Box isolation, sinus rhythm was restored by transthoracic cardioversion.…”
Section: Catheter Ablationmentioning
confidence: 99%
“…PV isolation or box isolation alone is effective for treating paroxysmal AF, 1,28,29) however, not enough for cure of persistent AF or longstanding persistent AF. 30,31) To improve the clinical outcome, extensive ablation, including multiple linear lesions and/or ablation of complex fractionated atrial electrograms (CFAE), has been widely adopted, particularly in patients with persistent AF or longstanding persistent AF.…”
Section: Ablation Of Cfaementioning
confidence: 99%
“…Therefore, we developed a new approach for complete isolation of the posterior LA including all PVs, namely box isolation ( Figure 1). 28) In the posterior LA, there are many arrhythmogenic substrates for AF, including the ganglionated plexi, reentries and triggers. Box isolation can contain these abnormal substrates in the posterior LA.…”
Section: Advantages Of Box Isolationmentioning
confidence: 99%
“…Our box isolation technique is conducted by means of a non-contact mapping system (NCM) or an electro-anatomical mapping system. 12, 13 Box isolation offers a feasible and safe AF treatment with longterm efficacy. Our results suggest that autonomic denervation by box isolation may cure AF, but data on long-term effects…”
mentioning
confidence: 99%